Peran Orang Tua dalam Upaya Pemeliharaan Kesehatan Gigi terhadap Kejadian Karies Gigi pada Anak Usia 6-9 Tahun di SDN 169 Pekanbaru - Isnaniar; Norlita, Wiwik; Anggraeni, Vivi (Fakultas MIPA dan Kesehatan, Universitas Muhammadiyah Riau, 2023)
Dental caries is a decayed area inside the tooth that occurs due to a process that gradually dissolves enamel (the hard outer tooth surface) and continues to develop to the inside of the tooth. One of the causes of dental caries is the role of parents in efforts to maintain dental health. Study results say that parental psychosocial factors that have been shown to negatively impact children's oral health include maternal depression, low coherence, pampering parenting and stressed parents. Parents' concern for children's dental health can be seen through their attitude and attention to children's dental health. The purpose of the study was to determine